Induction chemotherapy for locally advanced nasopharyngeal carcinoma treated with concurrent chemoradiation: A systematic review and meta-analysis - Tan, Teng Hwee (ELSEVIER IRELAND LTD, 2021)
10.1016/j.radonc.2018.02.027